A Pragmatic Randomized Comparative Trial of e-Cigarettes and Other Nicotine Products for Quitting or Long-Term Substitution in Smokers. Issue 7 (20th December 2021) - Morphett, Kylie; Fraser, Doug; Borland, Ron; Hall, Wayne; Walker, Natalie; Bullen, Chris; Gartner, Coral
Abstract: Introduction: Tobacco harm reduction has potential to improve individual and population health. However, little research exists on low-intensity interventions, such as encouraging longer-term NRT or e-cigarette use. We aimed to determine whether: (1) encouraging use of nicotine products as long-term tobacco substitutes is more effective for smoking abstinence than standard treatment, and (2) offering e-cigarettes is more effective than NRT. Methods: An open-label, parallel-group randomized trial was conducted in Australia between 2014 and 2015, with 1563 adult daily smokers, randomized to: (A) standard cessation advice and NRT: advice to use NRT short-term, (B) quit or substitute advice and NRT: advice to use NRT as a longer-term substitute for smoking if required to maintain smoking cessation, or (C) Quit or substitute advice and NRT and/or e-cigarettes. Participants were offered an initial supply of products they could then purchase for up to 7 months. The primary outcome was self-reported continuous smoking abstinence at 7 months. Point prevalence, dual use, and cigarette reduction were secondary outcomes. Results: At 7 months, 2.8% ( N = 9) of group A ( N = 324) were abstinent, compared with 1.8% ( N = 11) in B ( N = 620) and 1.3% ( N = 8) in C ( N = 619) (adjusted odds ratio [ORs]: B vs. A 0.66, 95% confidence interval [CI]: 0.27−1.63; C vs. A 0.46, 95% CI: 0.17−1.21; C vs. B 0.69, 95% CI 0.27–1.73). There were no suspected unexpected serious adverse reactions associated with trial products. Conclusion: A free trial of NRT and first generation e-cigarettes and advice on long-term substitution was no better for smoking abstinence than usual care. Clinical Trial Registration: The trial was registered with the Australian Therapeutic Goods Administration under their Clinical Trials Notification scheme and the Australian and New Zealand Clinical Trials Registry (ACTRN12612001210864). Implications: This pragmatic trial allowed the comparison of existing and alternative policy options under semi-realistic conditions, such as product choice and financial cost. All trial arms had low rates of smoking cessation. The findings suggest that providing unflavored cigalike e-cigarettes without additional support may not increase quitting compared with advice to use standard NRT in a general population of Australians who smoke. More intensive support and education, and/or opportunity to try a range of e-cigarette products, may be required to motivate quit attempts using e-cigarettes.